Detection of Rabies Antigen in the Saliva and Brains of Apparently Healthy Dogs Slaughtered for Human Consumption in Abia State Nigeria and its Public Health Implication. - Ogunkoya, A.B.,, 1Mshelbwala, P.P., 1; Abdullahi, S.U, Maikai, B.V. ,3 Nlebedum, UC (Journal of Medical Biomedical and Applied Sciences, 2014)
Apparently healthy dogs could excrete rabies virus in their saliva for long period without showing signs and symptoms of the disease. Carrier status of rabies virus infection has been demonstrated in different parts of Nigeria but in Abia State, there is limited information on the status of rabies in apparently healthy dogs. The study was carried out in eight slaughter points within four Local Government Areas of the State for the determination of rabies antigen in the saliva and brain of apparently healthy dogs slaughtered for human consumption. A total of one hundred (100) samples of saliva and brain were collected before and after slaughter respectively between April to June, 2013 in the selected areas. The saliva was subjected to rapid immune-chromatographic test (RICT) while Direct Fluorescent Antibody Test (DFAT) was carried out on the brain samples. Structured questionnaire was administered to nineteen (19) dog meat processors (18 male and 1 female) in the selected areas. Sixty four percent of the samples tested were from female dogs while 36% were from males. All the dogs were sourced from surrounding villages.  Five (5%) of the dogs tested were positive for rabies antigen with the use of both tests, signifying a total agreement between RICT and conventional DFAT. All the positive cases were detected in female dogs. 94.7% of the butchers were bitten during the course of processing, out of the 94.7% exposed to dog bite, 72.8%  utilize  traditional method of treatment while 27.8%  reported to the  hospital for proper medical attention. This study has established the presence of rabies antigen in apparently healthy dogs in the study area which may signify the endemicity of the disease in the area. Hence mass enlightenment program for dog owners, marketers, processors, consumers and children within the state is highly recommended.